PERAN MUDIR DALAM MEMBINA SANTRI MENJADI KADER ULAMA DI PONDOK PESANTREN DARUL AMIN PASAMAN BARAT - Habibi, Asmar; Julhadi, Julhadi; Rahmi, Rahmi (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2025)
Islamic Boarding Schools play a crucial role in producing future Islamic scholars (ulama) who not only master religious knowledge but also possess moral integrity and leadership qualities. However, challenges such as the lack of generational succession among mudirs (pesantren leaders) and the influence of globalization hinder the effectiveness of the cadre development process. This study aims to analyze the strategies employed by mudirs in nurturing students (santri) into future ulama, identify supporting and inhibiting factors, and formulate an adaptive leadership model for pesantren. Using a qualitative case study approach, data was collected through in-depth interviews, participatory observation, and document analysis at Darul Amin Islamic Boarding School in West Pasaman. The findings reveal that mudirs serve as curriculum designers, motivators, and role models, employing key strategies such as exemplary behavior, habituation, and personal mentoring. Cadre development programs including multilingual sermons (ceramah), Qur’an memorization (tahfiz), and practical da’wah training prove effective in shaping students' competencies. The main challenges include limited human resources, funding constraints, and geographic isolation, with solutions focusing on recruiting qualified teachers, stakeholder partnerships, and leveraging technology. The study concludes that Islamic values-based transformational leadership by mudirs is the key to successful ulama cadre development. The implications highlight the need to strengthen a holistic leadership model in pesantren and integrate traditional and modern approaches to address challenges in the digital era.